Unboxing empathy: reflecting on architectural design for maternal health. Issue 2 (3rd April 2022) - Sandman, Helena; Meguid, Tarek; Levänen, Jarkko
ABSTRACT: Co-design aims to bring designers and end-users together to improve the quality of design projects. In this paper, we study how the distance between designers and users can be reduced with an empathic approach particularly in settings where it is significant. By investigating various approaches on empathy in design and architecture, we were able to retrospectively understand different aspects of the design process of a maternity ward project in which we were involved. Engaging a theoretical clarification of empathy as a multi-dimensional concept made it possible to empirically explicate diverse difficulties that designers face when trying to employ empathy as a guiding philosophy in their work. As a result, we identified three registers of empathy on a varying scale of depth that can be integrated in the design process. Our work shows that various registers of empathy can complement each other or be utilised in different circumstances where one form might be more appropriate than another. By presenting these registers, we seek to unbox the different views on empathy and draw attention to the potential of empathic engagement when aiming for depth in a project.